Ocean-atmosphere interactions of gases and particles - Johnson, Martin T.; Liss, Peter S. (Springer Earth System Sciences, 2014)
The oceans and atmosphere interact through various processes, including the transfer of momentum, heat, gases and particles. In this book leading international experts come together to provide a state-of-the-art account of these exchanges and their role in the Earth-system, with particular focus on gases and particles.  Chapters in the book cover: i) the ocean-atmosphere exchange of short-lived trace gases; ii) mechanisms and models of interfacial exchange (including transfer velocity parameterisations); iii) ocean-atmosphere exchange of the greenhouse gases carbon dioxide, methane and nitrous oxide; iv) ocean atmosphere exchange of particles and v) current and future data collection and synthesis efforts. The scope of the book extends to the biogeochemical responses to emitted / deposited material and interactions and feedbacks in the wider Earth-system context.   This work constitutes a highly detailed synthesis and reference; of interest to higher-level university students (Masters, PhD) and researchers in ocean-atmosphere interactions and related fields (Earth-system science, marine / atmospheric biogeochemistry / climate).  Production of this book was supported and funded by the EU COST Action 735 and coordinated by the International SOLAS (Surface Ocean- Lower Atmosphere Study) project office.